Broken Windows: Why Culture Matters in Corruption Reform. Issue 1 (March 2016) - Hira, Anil
Corruption, or misuse of public office for private gain, is continually in the headlines. From hunger strikes in India to scandals around defence procurement in Canada, attention to corruption is growing. Corruption has been linked to weak economic growth and development outcomes (Kulshreshtha, 2008, p. 558). Though the problems of corruption have led aid agencies to recognize the fundamental importance of good governance, progress has been halting. In fact, there are almost no cases of a developing ('post-colonial') country moving from a highly corrupt situation to one in which corruption is minimized. Civil service reforms and elections of pro-reform candidates seem futile to bring long-lasting results in countries as diverse as India and Argentina. Failing states from Afghanistan to Iraq reveal corruption to be a central issue. While the role of culture, often defined as shared beliefs, attitudes, values, norms and practices is recognized in the academic literature as an element of potential importance, to date it has not been incorporated into the design of aid programmes to reform civil services. In this collection, we examine why attempts to reform the civil services of developing countries have largely failed in good part because they focus on the formal and ignore the need to reform culture as well. Our case studies including Singapore, Hong Kong, Chile, Afghanistan, Swaziland, India and Nigeria span a wide range of failures as well as a few success stories and are based on strong author knowledge of the local context as well as field research.